Analytic non-adiabatic couplings for the spin-flip ORMAS method. Issue 3 (23rd December 2019) - Mato, Joani; Gordon, Mark S.
Abstract : Analytic non-adiabatic coupling matrix elements (NACME) are derived and implemented for the spin-flip occupation restricted multiple active space configuration interaction (SF-ORMAS-CI) method. Abstract : Analytic non-adiabatic coupling matrix elements (NACME) are derived and implemented for the spin-flip occupation restricted multiple active space configuration interaction (SF-ORMAS-CI) method. SF-ORMAS is a general spin correct implementation of the SF-CI method and has been shown to correctly describe various stationary geometries, including regions of conical intersections. The availability of non-adiabatic coupling allows a fuller examination of non-adiabatic phenomena with the SF-ORMAS method. In this study, the implementation of the NACME is tested using two model systems, MgFH and ethylene. In both cases, the SF-ORMAS method exhibits good qualitative agreement with established multi-reference methods, suggesting that SF-ORMAS is a suitable method for the study of non-adiabatic chemical phenomena.